Lessons from a Successful Implementation of a Computerized Provider Order Entry System - Jacobs, Brian R. (Pediatric Pharmacy Advocacy Group, 2007)
OBJECTIVES: The electronic health record (EHR) can improve patient safety, care efficiency, cost effectiveness and regulatory compliance. Cincinnati Children's Hospital Medical Center (CCHMC) has successfully implemented an Integrating Clinical Information System (ICIS) that includes Computerized Provider Order Entry (CPOE). This review describes some of the unanticipated challenges and solutions identified during the implementation of ICIS. METHODS: Data for this paper was derived from user-generated feedback within the ICIS. Feedback reports were reviewed and placed into categories based on root cause of the issue. Recurring issues or problems which led to potential or actual patient injury are included. RESULTS: Nine distinct challenges were identified: 1) Deterioration in communication; 2) Excessive system alerts to users; 3) Unrecognized discontinuation of medications; 4) Unintended loss of orders; 5) Loss of orders during implementation; 6) Amplification of errors; 7) Unintentional generation of patient care orders by system analysts; 8) Persistence of specific patient care order instructions; 9) Verbal orders entered under the incorrect clinician. CONCLUSIONS: Unanticipated challenges are expected when implementing EHRs. The implementation plan for any EHR should include methods to identify, evaluate and repair problems quickly. While continued challenges with this complex system are expected, we believe that the EHR will continue to facilitate improved patient care and safety. The lessons learned at CCHMC will permit other institutions to avoid some of these challenges and design robust processes to detect and respond to problems in a timely fashion to ensure implementation success.